Analysis of The Implementation of The Independent Curriculum in Elementary School - Hairunnisa Hairunnisa; Sarippudin Sarippudin; Mega Riyawati (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
This research aims to analyze the implementation of the Merdeka Curriculum at SD Negeri 005 Tanjungpinang Timur, focusing on textbook availability, teaching strategies, technology use, teacher professional development, challenges, and solutions. Using interviews, observations, and document analysis, the study found that despite challenges such as resource limitations and the need for additional teacher training, the school has made efforts to overcome these obstacles. Most textbooks align with the Merdeka Curriculum, though some teachers still use older materials as references. Teachers have adopted interactive and innovative teaching strategies, utilizing technology to enhance learning. The study concludes that while the implementation is going well, some improvements and adjustments are needed. This research contributes positively to the school's educational development and can serve as a reference for other schools implementing the Merdeka Curriculum.